THE INCIDENCES OF THE GLOBAL CRISIS ON THE INTERNATIONAL TRADE IN GOODS - Mariana MIHĂILESCU (Strategii Manageriale)
Having its origins in the excesses occurred in the Western financial system, the global crisis has affected the world economic circuit as a whole and thus its most dynamic flux: the international trade in goods. After the sharp and synchronized downturn of the transactions in 2009, the world trade in goods experienced a revival in 2010 and, again, a slowdown in growth in 2011. The emphasis on the protectionist tendencies in 2012 and the keeping of the risk factors surrounding the global economy maintain not a very optimistic perspective in this area. This paper reflects the evolution of the international trade in the current period as well as the changes occured in the hierarchy of the major retailers in the world. Also, the highlighting of the factors that caused increase and decrease oscillations to the global trade represents the main objective of this theme.